Health Education for Musicians - Matei, Raluca; Broad, Stephen; Goldbart, Juliet; Ginsborg, Jane (Frontiers in Psychology, 2018)
Context and aims: Many musicians suffer for their art, and health is often compromised during training. The Health Promotion in Schools of Music (HPSM) project has recommended that health education should be included in core curricula, although few such courses have been evaluated to date. The aim of the study was to design, implement and evaluate a compulsory health education course at a UK conservatoire of music. Methods: The course design was informed by a critical appraisal of the literature on musicians’ health problems and their management, existing health education courses for musicians, and the HPSM recommendations. It was delivered by a team of appropriately-qualified tutors over five months to 104 first-year undergraduate students, and evaluated by means of questionnaires at the beginning and end of the course. Thirty-three students who had been in their first year the year before the course was introduced served as a control group, completing the questionnaire on one occasion only. Items concerned: hearing and use of hearing protection; primary outcomes including perceived knowledge and importance of the topics taught on the course; and secondary outcomes including physical and psychological health and health-promoting behaviours. The content of the essays written by the first-year students as part of their course assessment served as a guide to the topics they found most interesting and relevant. Results: Comparatively few respondents reported using hearing protection when practising alone, although there was some evidence of hearing loss, tinnitus and hyperacusis. Perceived knowledge of the topics on the course, and awareness of the risks to health associated with performing music, increased, as did self-efficacy; otherwise, there were negative effects on secondary outcomes, and few differences between the intervention and control groups. The topics most frequently covered in students’ essays were managing music performance anxiety, and life skills and behaviour change techniques. Conclusion: There is considerable scope for improving music students’ physical and psychological health and health-related behaviours through health education, and persuading senior managers, educators and students themselves that health education can contribute to performance enhancement.